Boundary value problems with solutions in convex sets - Gerd Herzog; Peer Chr. Kunstmann (Opuscula Mathematica, 2019)
By means of the continuation method for contractions we prove the existence of solutions of Dirichlet boundary value problems in convex sets. As an application we prove the existence of concave solutions of certain boundary value problems in ordered Banach spaces.